Conceptual Model of Utilizing the Competitive Ability of Maritime Transport in the Economic Security System - Laiko, O.; Khumarova, N.; Ilchenko, S.; Gryshchenko, V.; Gryshchenko, I. (Science and Innovation, 2023)
Introduction. In order to function successfully in the market, the water transport business entities, in addition to material and financial resources, need the utilization of their internal unique capabilities in the existing business environment, which determine the competitive potential. Problem Statement. The successful operation and development of water transport requires the development of a scientific approach to utilizing its competitive potential in the country’s economic security system. Purpose. The purpose of this research is to form a conceptual model of the utilization of competitive potential of water transport in the economic security system of the Black Sea region. Material and Methods. We have used the following methods: system structural, abstract logical analysis, grouping, and economic mathematical modeling, for studying the essence and structure of the competitive potential of water transport, for assessing its utilization in security system of the Black Sea region. Results. The essence of the category “competitive potential of water transport” has been determined. The structure of the competitive potential of water transport has been studied, and the conceptual model of its use in the economic security system has been developed. Based on the proposed conceptual model, the utilization of the competitive potential of water transport in the economic security system has been assessed by the example of the Black Sea region. Conclusions. In order to enhance the competitive potential of water transport of Ukraine and the level of its utilization, in the context of economic security, it has been proposed to stimulate an increase in the number of ship calls to the ports of Ukraine and the number of Ukraine-flagged vessels belonging to domestic businesses and to create favorable conditions for the development of the shipbuilding industry of Ukraine.